Synthesis, Spectral Characterization and Crystal Structure of Chlororhodibalamin: A Synthesis Platform for Rhodium Analogues of Vitamin B12 and for Rh-Based Antivitamins B12 - Widner, Florian J.; Kieninger, Christoph; Wurst, Klaus; Deery, Evelyne; Lawrence, Andrew D.; Warren, Martin J.; Kräutler, Bernhard (Synthesis, 2020)
Chlororhodibalamin (ClRhbl), a rhodium analogue of vitamin B12 (cyanocobalamin), was prepared in 84% yield by metalation of the metal-free B12 ligand hydrogenobalamin using the RhI-complex [Rh(CO)2Cl]2. ClRhbl was identified and characterized by UV/Vis, circular dichroism, high-resolution mass and heteronuclear NMR spectra. The RhIII-corrin ClRhbl features the ‘base-on’ architecture of vitamin B12. X-ray analysis of single crystals of ClRhbl have revealed its detailed 3D-geometry and close structural similarity to the CoIII-analogue chlorocobalamin (ClCbl). ClRhbl is a versatile starting material for the preparation of other rhodibalamins, among them the organometallic derivatives adenosylrhodibalamin and methylrhodibalamin, the Rh analogues of the important coenzyme and cofactor forms of B12, adenosylcobalamin and methylcobalamin.
Keywords: rhodium; transition metals; vitamins; porphyrins; natural products; antivitamin; metalation; inhibitors